THE ROLE OF KKN STUDENTS IN DEVELOPING INNOVATIVE LEARNING METHODS AT SMPN SATAP 9 PESAWARAN - Nasution, Sri Ilham; Wibowo, Syahra Vaiola (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is the main basis for the development of society and the country. The Community Service Program (KKN) is one way to involve students from universities in improving the quality of education in certain areas. This research aims to examine the role of Real Work Lecture (KKN) students in developing innovative learning methods at SMPN Satap 9 Pesawaran. Education is an important aspect in community development, but many challenges are faced by educational institutions, including less attractive learning methods and low student engagement. Through a qualitative approach, data is collected through observation, interviews, and documentation to understand the experiences of KKN students and their impact on the learning process. The research results show that KKN students have succeeded in implementing innovative learning methods, such as project-based learning and cooperative learning, which can increase student motivation and involvement. KKN students play an active role in the teaching and learning process. They not only act as observers but also as facilitators who help improve learning methods. KKN students contribute to teaching training, assist, and create an interactive learning atmosphere by using creative learning strategies. Apart from that, they also implement programs aimed at increasing students' interest in learning, including learning activities outside of school and providing motivation. However, KKN students also face various challenges, including differences in student learning styles, limited technological knowledge, and obstacles. Resource. The conclusions of this research emphasize the importance of appropriate support for KKN students so that they can continue to make positive contributions in improving the quality of education at SMPN Satap 9 Pesawaran. It is hoped that innovation in learning methods will continue and have a significant impact on students, teachers, and society.